The 2005th Amman Message: Significant Reference for Nusantara Ulama to Enlarge the Existing Indonesian Plurality - Hadri Hasan; D I Ansusa Putra (Millati: Journal of Islamic Studies and Humanities, 2018)
The Amman Message signed by 500 Ulama from Moslem countries, both Shia and Sunni, on the 27th of Ramadan 1425 H or 9 November 2004 in Amman, Jordan. This declaration is a reaction to the widespread fragmentation and decentralization of Muslim identity. The Amman Message positioning Islamic valued vis-a-vis the dynamic modern world. The method used in this research was tracing the content of the book of Risalat Amman (Amman Message), especially to the Ulama consensus related to the topic of pluralism. As an Islamic scholars consensus from all over the world, the Amman Message discussed and decided some opinions on plurality. This article would parse the significance of this message and its contribution to the Indonesian Islamic scholars’ perspective in perceiving the plurality existing in Indonesia modern world, within the Indonesian Islam and in context Indonesia cross religion discourse and dialogue intra-religion concept.